FACTORS ASSOCIATED WITH DEPRESSION AMONG MEDICAL STUDENTS IN A MEDICAL SCHOOL DURING THE COVID-19 PANDEMIC - Gilang Samudero; Hadiyanto Hadiyanto; Dharmady Agus (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: The impact of the COVID-19 outbreak caused mental health problems, one of which is the depression. This study analyzed the factors associated with depression among medical students in a medical school during the COVID-19 pandemic. This study aimed to assess the factors associated with depression during the COVID-19  pandemic such as gender, the year of student, the residence during COVID-19 pandemic, the risk of infecting others, quarantine, and social distancing or physical distancing.Methods: Cross-sectional study was conducted on 185 preclinic medical students of School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. Data was collected using the identity of participants, Depression Anxiety Stress Scale (DASS 42), and Patient Health Questionnaire (PHQ-9). Chi-square analysis were applied for this study, if the chi-square analysis did not meet the requirements, the researcher had to use the fisher exact test as an alternative test. Researcher also performed logistic regression analysis to determine the most significant factor.Results: The result of study showed that the year of student had the most significant relationship with depression measured by DASS 42 (p:0,043) and PHQ-9 (p:0,006) and the higher year of student or the higher semester of student had the decrease depression measured by DASS 42 (coef: -0,46; OR: 0,63; 95% CI: 0,406-0,985) and PHQ-9 (coef: -0,53; OR: 0,58; 95% CI: 0,404-0,858) with logistic regression analysis Conclusion: The year of student has the most significant relationship with depression .